Near-tip strain ratchetting and crack growth at elevated temperature. (January 2016) - Tong, J.; Cornet, C.; Lin, B.; Lupton, C.; Li, H.-Y.; Bowen, P.; Williams, S.; Hardy, M.
Highlights: Ratchetting strain predicted fatigue crack growth in vacuum for the first time. Accumulated inelastic strain predicted well FCGR of nickel alloy from 550 to 775 °C. Unified constitutive model used for prediction of CGR under fatigue/fatigue+creep. Abstract: In this work, we have extended our earlier work on the concept of ratchetting strain as a crack driving force (Tong et al., 2013), to examine the crack growth of a nickel-based superalloy at selected temperatures in vacuum under both fatigue and fatigue-creep loading conditions. The parameters of a unified constitutive model were calibrated against the material data obtained at selected temperatures from 550 to 775 °C, and a finite element model was developed to simulate the near-tip stress–strain responses under fatigue and creep-fatigue loading conditions at the experimental temperatures. Both ratchetting strain and accumulated inelastic strain near the crack tip were utilised in the prediction of the crack growth rates collected in vacuum. It seems that, although both ratchetting strain and accumulated inelastic strain correlate with the crack growth rates obtained under fatigue and fatigue-creep loading conditions, the predictions based on accumulated plastic strain are particularly close to the experimental results at all temperatures and loading conditions examined. This is the first time the concept of ratchetting strain has been used to predict the crack growth rates of an engineering alloy at elevated temperature in vacuum, where the influence of oxidation on crack growth is removed.